The philosophy of perception : proceedings of the 40th International Wittgenstein Symposium - Stadler, Friedrich; Limbeck-Lilienau, Christoph (Berlin : Walter de Gruyter, 2021)
This volume features discussions on the philosophy of perception and observation by leading philosophers, exploring their implications for the philosophy of mind, epistemology, and the philosophy of science.
Includes index.
Keywords: Illusion (Philosophy).; Perception (Philosophy) - Congresses; Wittgenstein, Ludwig, 1889-1951 Congresses